The Gender Gap in UK Academic Economics 1996-2018: Progress, Stagnation and Retreat - Victoria Bateman; Erin Hengel (Œconomia, 2023)
This article reports on women’s representation in UK economics over the last quarter century. While progress has been made, women in 2018 were only 32 percent of economics undergraduate students and 26 percent of academic economists. Our data also suggest several areas of stagnation and retreat. First, the percentage of female UK nationals studying economics is low and falling over time. Second, female economists are substantially more likely to be employed at lower academic ranks and in fixed-term—and generally lower status—teaching- and research-only positions. Third, the representation of women is especially low among ethnic minorities studying for an economics PhD. And finally, the percentage of economics professors with Asian ethnicity who are women has been falling over time, and at no point between 2012-2018 was a Black female professor of economics employed anywhere in the UK.